Platelet Rich Fibrin as a Potential Treatment for Corneal Neovascularization due to Infective Keratitis: An Experimental Study: Oral Presentation - Experimental Study - Resident - NANDANG SUDRAJAT (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Platelet-rich fibrin (PRF) as a source of growth factor has been widely used in various therapeutic fields so that it could accelerate the wound healing process. This study investigated the effect of platelet-rich fibrin PRF in inhibiting neovascularization, inhibiting the expression of vascular endothelial growth factor (VEGF) and stimulating pigment epithelial-derived factor (PEDF) in the infective keratitis animal model. Methods : A total of 12 New Zealand white rabbits (Oryctalogus cuniculus) were subjected to keratitis induction by inoculation of Pseudomonas aeruginosa. The rabbits were divided into two groups, the first group as control was treated antibiotic-only, and the second as treatment group was treated with antibiotic and PRF graft. The corneal neovascularization area was clinically measured before and after treatment. Expression of VEGF and PEDF in the corneal epithelium, stroma, and endothelium were evaluated by immunohistochemical examination on day 10 after keratitis induction. Results : There were significant differences in VEGF expression between groups in the epithelial layer (p=0.008), but no significant difference in the stromal (p=0.934) and endothelial (p=0.935) layers. PEDF expression showed a significant difference between groups in the epithelial (p = 0.004) and stroma layers (p = 0.029) but no significant difference in the endothelial layer (p = 0.157). However, there was no significant difference in clinical neovascularization between the two groups (p=0.526). Conclusion : PRF could inhibit VEGF expression and stimulate PEDF expression in the cornea of Pseudomonas aeruginosa keratitis animal model that potentially reduces the corneal neovascularization in the longer observation.